Ameliorative effect of Lacticaseibacillus rhamnosus Fmb14 from Chinese yogurt on hyperuricemia - Hongyuan Zhao; Xiaoyu Chen; Fanqiang Meng; Libang Zhou; Xinyi Pang; Zhaoxin Lu; Yingjian Lu (Food Science and Human Wellness)
Hyperuricemia is a critical threat to human health, and a high inosine diet can increase the prevalence of it. Lacticaseibacillus rhamnosus Fmb14 was isolated from traditional fermented Chinese yogurt, and its inosine degradation rate reached 36.3 % at 109 CFU/mL for 24 h. LC-MS analysis revealed that high concentrations of inosine could activate compensatory metabolic pathways of L. rhamnosus Fmb14 to catalyse inosine as an energy source and produce intracellular folic acid and riboflavin. The contents of folic acid and riboflavin were 6.0 and 4.3 fold increased after inosine treatment in the cell-free extracts (CFE). L. rhamnosus Fmb14 CFE treatment ameliorates hyperuricemia through xanthine oxidase (XOD) inhibition and ATP-binding cassette subfamily G member 2 (ABCG2) promotion, both of which are responsible for uric acid (UA) synthesis and secretion in HepG2 and Caco2 cells, respectively. The in vivo results showed that the serum UA level decreased from 236.28 to 149.28 μmol/L after 8 weeks of oral administration of L. rhamnosus Fmb14 in inosine-induced hyperuricemia model mice. Our results revealed that L. rhamnosus Fmb14 has a potential as a biological therapeutic agent in hyperuricemia prevention.